Time For Poetry - Arbuthnot, May Hill. (Chicago Scott, Foresman and Company, 1952)
A representative collection of poetry for children, to be used in the classroom, home, or camp; especially planned for college classes in childrens literature; with an introduction for teachers and parents and notes on the presentation of individual poems.
Keywords: Poetry